The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1007/bf01875856
|View full text |Cite
|
Sign up to set email alerts
|

Male victims of child sexual abuse

Abstract: Despite the increased attention the subject of child sexual abuse has received in recent years, rarely has much consideration been given to the boys and adolescent males who are the victims of such abuse. That young girls are consistently the clear majority of sexual abuse victims is not disputed, however the extent to which they are the majority is in question. A review of existing literature has indicated that one of the leading factors for this inadvertent negligence in presenting a truer picture of the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
(34 reference statements)
0
25
0
2
Order By: Relevance
“…Although recent research reported prevalence rates of emotion maltreatment as approximately 14% for women and 10% for men (Scher, Forde, McQuaid, & Stein, 2004), it is plausible that men are underreporting their experience of emotional abuse. Certainly, previous research indicates that males underreport incidences of sexual and physical abuse (Cermak & Molidor, 1996) and in light of perceived lack of severity or tangible evidence of emotional abuse, underreporting might be even more likely.…”
Section: Downloaded By [Eindhoven Technical University] At 13:53 18 Nmentioning
confidence: 91%
“…Although recent research reported prevalence rates of emotion maltreatment as approximately 14% for women and 10% for men (Scher, Forde, McQuaid, & Stein, 2004), it is plausible that men are underreporting their experience of emotional abuse. Certainly, previous research indicates that males underreport incidences of sexual and physical abuse (Cermak & Molidor, 1996) and in light of perceived lack of severity or tangible evidence of emotional abuse, underreporting might be even more likely.…”
Section: Downloaded By [Eindhoven Technical University] At 13:53 18 Nmentioning
confidence: 91%
“…Reviews of prevalence research have estimated that anywhere between 2.5 and 36.9% of males, and between 6 and 62% of females may have been subjected to sexual abuse in childhood (Dhaliwal, Gauzas, Antonowicz, & Ross, 1996;Finkelhor, 1986). Furthermore, retrospective self-reports show a much higher proportion of male victims than official reports do, suggesting significant underreporting by male victims (Cermak & Molidor, 1996;Etherington, 1995). Not surprisingly, then, a key finding of the Queensland Crime Commission and Queensland Police Service (2000) report on child sexual abuse was the low level of disclosure, especially by boys, resulting in a recommendation by the Commission for a survey of male victims and survivors of childhood sexual abuse to uncover the impediments to disclosure.…”
Section: Introductionmentioning
confidence: 90%
“…A recent review of research by Paine and Hansen (2002) showed that the rate of nondisclosure among boys increases with age, leading these and other authors to suggest that boys may be reluctant to disclose because of factors related to male socialization, such as an overemphasis on self-reliance, contempt for victims and homosexuals, sexual prowess, and masculine obsession with heterosexuality and independence (Black & De Blassie, 1993;Cermak & Molidor, 1996;Dhaliwal et al, 1996;Finkelhor et al, 1990;Nasjleti, 1980;Nelson & Oliver, 1998;Paine & Hansen, 2002;Roane, 1992;Sebold, 1987;Spataro, Moss, & Wells, 2001;Watkins & Bentovim, 1992, 2000. The implication of a study by Fondacaro, Holt, and Powell (1999) is that some male victims may be confused about what precisely constitutes sexual abuse.…”
Section: Introductionmentioning
confidence: 96%
“…In fact, in the literature prior to 1980, it is rare to find any reference to MCSA at all. Clinicians working with sexual abuse survivors, the professional and research literature, and the media have portrayed CSA as a phenomenon that almost exclusively involves female victims and male perpetrators (Cermak and Molidar 1996). The research on MCSA is limited but what is available consistently shows that the sexual victimization of males does occur at significant rates (Cawson et al 2000;Fergusson et al 1996;Finkelhor 1994;Putnam 2003;Rind et al 1998).…”
Section: Introductionmentioning
confidence: 97%